2016
DOI: 10.1186/s12967-016-0851-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of the Mediterranean diet on mortality in individuals at low cardiovascular risk: a 12-year follow-up population-based cohort study

Abstract: BackgroundAdherence to the Mediterranean diet reduces the risk of all-cause and cardiovascular (CV) mortality and the incidence of CV events. However, most previous studies were performed in high-risk individuals. Our objective was to assess whether the adherence to the Mediterranean diet, evaluated by the MED score, was associated with all-cause and CV mortality and incidence of CV events in individuals at low CV risk from a population-based cohort, after a 12-year mean follow-up.MethodsA cohort of 1658 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…In a model adjusted for confounding factors, the “Healthy” pattern was associated to low occurrence of abdominal obesity, dyslipidemia, diabetes, and hypertension. This pattern resembles other cardioprotective patterns described in the literature and associated with low disease risk [15, 51, 52] and low mortality [5355]. Therefore, the protective effect of this pattern is well established.…”
Section: Discussionsupporting
confidence: 83%
“…In a model adjusted for confounding factors, the “Healthy” pattern was associated to low occurrence of abdominal obesity, dyslipidemia, diabetes, and hypertension. This pattern resembles other cardioprotective patterns described in the literature and associated with low disease risk [15, 51, 52] and low mortality [5355]. Therefore, the protective effect of this pattern is well established.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, the summary RR for the nine MedDiet components are generally in agreement with the current literature. Several studies have reported the survival benefit (25) 2006 (30) 2007 (31) 2010 (32) 2012 (36) 2012 (37) 2015 (40,41) 2014 (39) 2017 (7) 2018 (47) 2015 (40,41) 2016 (6,42,43) 2018 (26) 1995 (27) 1999 (13) 2000 (28) 2004 (29) 2005 (25) 2006 (30) 2009 (4) 2010 (32) 2016 (20,42,43) 2017 (7,44,45,46) Time (year) Time (year) 2011 (33,34,35) 2011 (33,34,35) 2014 (22,23,38) Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…The studies analysed by Sofi et al (4) were also included in the current meta-analysis, except for the study by Martínez-González et al (8) , as the most recent publication by Alvarez-Alvarez et al (29) used the same cohort and was more informative. Therefore, thirty articles were finally included in the meta-analyses of the MedDiet with all-cause mortality: fourteen published before (7,16,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and sixteen published after June 2013 (up to 31 December 2017) (9,10,23,25,26,29,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) . Detailed characteristics of these studies are shown in Table 1.…”
Section: Sixteen Articles Remainedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mediterranean diet has been reported to be effective for preventing non-communicable diseases [12][13][14][15] and reducing overall mortality and the incidence of several cancers [16,17]. It is generally characterized by a high consumption of fruits, vegetables, legumes and cereals, moderate-to-high consumption of fish, moderate consumption of alcohol (mostly wine), low-to-moderate consumption of milk and dairy products, and low consumption of meat and meat products [18].…”
Section: Introductionmentioning
confidence: 99%